Book Review - Dasgupta, Anindita (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
The Trauma and the Triumph: Gender and Partition in Easter India, (Ed.) Jasodhara Bagchi Subhoranjan Dasgupta. First publsihed in February 2003 by STREE, Kolkata, India. Pp. 272. ISBN 81-85604-55-X